Building Social Harmony through Religious and Cultural Approaches in Jorong Dusun Tuo - Azhari, Camelia; Wahyuni, Sri; Ayunda Salsabila, Deby; Roihanah Nasution, Fitri; Zaneti, Harsa; Mutiara Diva, Natasya; Nurhuda, Khairina; Nandika, Mutia Dwi; Prayoga, Muhammad Gusti; Diva, Natasya Mutiara; Syaputra, Raziz; Ahmadi, Syafira Risti; Indriani, Winda; Febrian, Zaki (Mangabdi: Journal of Community Engagement in Religion, Social, and Humanities, 2025)
Social harmony is a crucial foundation for sustainable community life, particularly in religiously oriented communities where latent social fragmentation may emerge despite shared beliefs. This article examines a community empowerment initiative aimed at strengthening social harmony through religious and cultural approaches in Jorong Dusun Tuo, Nagari Limo Kaum. The program employed a participatory community empowerment approach that positioned community members as active agents in addressing social distance between two congregations with limited interaction. Religious engagement and local cultural activities were utilized as primary instruments for fostering inclusive interaction, trust-building, and collective participation. Data were collected through participatory observation, informal interviews, and reflective discussions, and analyzed descriptively to capture changes in social relations and community dynamics. The findings indicate that the integration of religious and cultural approaches effectively reduced social barriers, enhanced intergroup communication, and strengthened social cohesion without undermining existing identities. Religious values provided ethical motivation for unity, while cultural practices created experiential spaces for cooperation. This study concludes that empowerment-oriented social interventions grounded in local religious and cultural contexts offer a practical and adaptable model for strengthening social harmony in communities experiencing latent fragmentation.